Economics of sea buckthorn production and processing in Hungary - Erdős, A. D.; Szőllősi, L. (International Journal of Horticultural Science, 2018)
This study focuses on the business management-related advantages and disadvantages of sea buckthorn production and processing based on economic analyses. It is the main objective of the authors to identify the expected economic findings in a high standard plantation with different average yields. A deterministic model calculation was performed on the basis of technological processes, using the primary data collected from enterprises dealing with sea buckthorn production. The calculation is based on the assumption of a 10 hectare plantation with intensive production technology (high soil quality (golden crown value: 32 GC per ha), irrigation, high plant density per hectare). The cost and income relations and the long-term return of the plantation were examined in the case of different average yields (12 t ha-1, 18 t ha-1 and 24 t ha-1). Under the economic circumstances of 2016, the planting cost of an intensive plantation is around 4-4.1 million HUF ha-1. In the years following the fruit-bearing stage, direct production costs are between 2.5-3.9 million HUF ha-1, depending on the given average yield. On the contrary, 5.6-11.1 million HUF ha-1 revenue can be reached based on the current market prices, resulting in a gross margin of 3.1-7.1 million HUF ha-1. Under the modelled circumstances, return is realised on the plantation’s costs in 6-8 years. The net present value (NPVr=3.24%) calculated for the 15-year-long life cycle of the 10-hectare plantation is between 151-466 million HUF, while the internal rate of return (IRR) is between 23-45%. From the business management aspect, the advantage of sea buckthorn production is that it provides better income and return at a planting cost which is similar to that of other small fruits and berries. At the same time, the disadvantage of sea buckthorn production is the fact that yields are harvested every two years due to the technological characteristics of harvesting. The negative impact of this bi-yearly yield on liquidity can be eliminated with the so-called delayed planting.